Visualizing time dependent semantics: an application to quantum algorithms - Kadaba, N.R.; Irani, P.P.; Toulouse, M. (Ninth International Conference on Information Visualisation (IV'05), 2005)
We have developed a visual syntax for representing concepts that are contingent on temporal properties (time-dependent semantics). A within-group (N=24) experiment was conducted to identify the representations that conveyed best a given semantic. We then applied our representations to the visualization of algorithms in quantum computing and carried out a second experiment (N=16) on subjects unfamiliar with the semantic concepts that were tested. The results show that our representations are intuitive and facilitate a good level of understanding of the algorithms.